2013
DOI: 10.1021/nn401946s
|View full text |Cite
|
Sign up to set email alerts
|

Analog Neuromorphic Module Based on Carbon Nanotube Synapses

Abstract: We report an analog neuromorphic module composed of p-type carbon nanotube (CNT) synapses and an integrate-and-fire (I&F) circuit. The CNT synapse has a field-effect transistor structure with a random CNT network as its channel and an aluminum oxide dielectric layer implanted with indium ions as its gate. A positive voltage pulse (spike) applied on the gate attracts electrons into the defect sites of the gate dielectric layer, and the trapped electrons are gradually released after the pulse is removed. The ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
74
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 21 publications
(40 reference statements)
0
74
0
Order By: Relevance
“…Different synaptic functions such as spike-timing dependent plasticity (STDP) and memory consolidation have been demonstrated in various memristors or memristive devices, such as oxides62122, chalcogenides823242526, ferroelectronics2728, field effect transistors2930 and carbon nanotubes3132. In these implementations, two terminals of the device are always regarded as the pre- and postsynaptic sites when inputting the voltage spikes, and the device conductance or resistance represents the synaptic weight that reflects the connection strength of neurons.…”
mentioning
confidence: 99%
“…Different synaptic functions such as spike-timing dependent plasticity (STDP) and memory consolidation have been demonstrated in various memristors or memristive devices, such as oxides62122, chalcogenides823242526, ferroelectronics2728, field effect transistors2930 and carbon nanotubes3132. In these implementations, two terminals of the device are always regarded as the pre- and postsynaptic sites when inputting the voltage spikes, and the device conductance or resistance represents the synaptic weight that reflects the connection strength of neurons.…”
mentioning
confidence: 99%
“…Perhaps most enticingly, some physical properties of these devices that depend on their previous states can be successively tailored by the external stimulus and be stored even after power-off, very analogous to the behaviours of the biological synapse. As a result, several nanoscale electronic devices that include metal oxides [22, 23], solid-electrolytes [24, 25], carbon nanotubes [26, 27], organic electronics [28, 29], spin transfer torque MRAM [30, 31], and phase-change memory (PCM) [32] based on the aforementioned technologies have been proposed to systematically mimic the biological function of the human brain, in particular the learning and memorization capabilities govern by the synapse. It should be noticed that due to the extremely complexity of the human brain, none of these available electronic devices has exhibited the promising potential to prevail or even meet the physical performances of the biological synapse to date.…”
Section: Reviewmentioning
confidence: 99%
“…Shen et al (2013) recently reported an analog neuromorphic module consisting of an integrate-and-fire circuit and p -type carbon nanotubes (CNTs) synapses. The CNTs synapse resembles a FET structure using as its gate an aluminum oxide dielectric layer implanted with indium ions and as its channel a random CNTs network.…”
Section: Nanomaterialsmentioning
confidence: 99%